Social Value Creation through Productive Zakat Management by Pesantren Cooperatives: A Case Study of Kopmu-DT Pesantren Daarut Tauhiid - Sukmawati, Ellies; Sumardjo, Sumardjo; Amanah, Siti; Maman, Ujang (UIN Sunan Kudus, 2026)
This study aims to determine the role of Kopmu-DT in creating social value for beneficiaries, identifying social value creation programs, and analysing the impact of social value creation programs on the welfare of beneficiaries. This approach uses qualitative and case-study designs. The data collection technique was carried out through in-depth interviews, observations, and documentation studies, and the validity of the results was validated using the triangulation technique. Based on the results of the study, it is known that the management of LAZNAS DT Peduli philanthropic funds is productively distributed by Kopmu-DT to its members in the form of initial capital and empowerment facilities. This innovation allows zakat not only to be distributed consumptively, but also managed as sustainable business capital. Social value creation is carried out through Islamic financial services, mentoring, business skills training, and business development support. This program has increased family income, independence as entrepreneurs, and strengthened Islamic values in members' entrepreneurial practices. Thus, this model can be considered an alternative for managing productive zakat to improve community welfare.